(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses and assesses the results of the construction of the Great Fergana Channel through a comprehensive analysis of the development and irrigation of virgin lands, the production of agricultural products and the increase of yields, and the efficient use of water resources of the BFC.